Clinical Response of Post-Encephalitic Dystonia to Trihexyphenidyl and Baclofen Therapy - Aye Mu Saan; Kyaw Linn (Myanmar Medical Journal, 2026)
"Abstract Background: Post-encephalitic dystonia is a common lifelong disability in children, with limited evidence guiding oral treatment options. This study aimed to evaluate clinical response of post-encephalitic dystonia to oral trihexyphenidyl and baclofen therapy in children. Methods: A hospital-based randomized comparative interventional study was conducted among 44 children with post-encephalitic dystonia, with 22 patients in each treatment group. Baseline socio-demographic data, clinical characteristics, dystonia features, and severity were recorded before treatment. Medications were administered using standard protocol and continued for 6 months in treatment-responsive cases. Efficacy was assessed using the Barry-Albright Dystonia Scale (BADS) at baseline, 3 months, and 6 months. Results: Baseline characteristics were comparable between groups except for gender. In the trihexyphenidyl group, mean BADS scores decreased from 13.5 ± 9.0 to 2.27 ± 3.3 and 1.4 ± 3.1 at 3 and 6 months, respectively. In